Wild man - Schneebaum, Tobias (Living Out: Gay and Lesbian Autobiog Ser., 2003)
Part autobiographical journal, part social-historical novel, Wild Man tracks Tobias Schneebaum's fascinating and almost epic life story, from his earliest contemplation of homoerotic desire through his life in Peru, Borneo, and beyond. A young man from New York, Schneebaum "disappeared" in 1955 on the eastern slopes of the Andes. He was, in actuality, living for more than a year among the remote Harakhambut people, discovering a way of being that was strange, primitive, and powerfully attractive to him. This longing to find the "wild man" in other cultures - and in himself - eventually led him on an odyssey through South America, India, Tibet, Africa, Borneo, New Guinea, and Southeast Asia. He lived among isolated forest peoples, including headhunters and cannibals, in regions where few, if any, white men had ever been